Research and Application of Network Virtualization Technology Based on OpenFlow - Hongguang Guan; Yizhen Yang; Wanli Ren; Zhijie Han; Yimu Ji; Yanfei Sun (Dianxin kexue)
Since the advent of OpenFlow, SDN technology research institutions at home and abroad have invested a great deal of research effort, such as the deployment of fully controllable and customizable network experiment platform. The programmable routing technology virtualization and the hardware devices of OpenFlow network have made certain progress. The OpenFlow technology research results based on the network virtualization field related were reviewed and compared briefly with the NFV technology. Else, a prospect of the OpenFlow technology application in the future research field and research direction was put forward.